Report on Hungarian students currently studying in the Austrian public school system without permanent residency in Austria (Training and Practice : Journal of Educational Sciences, 2020)
Currently approximately 2000 Hungarian-speaking children are studying in Austrian public schools, most of them commuting daily between their place of residence in Hungary and the school in Austria. In Austria, regardless of immigration status, an important criterion for attending school is an adequate level of knowledge of the language of instruction, German. The principles for the integration and language development of students with a non-German-speaking migrant background are set by the Austrian government at a national level. However, the situation of Hungarian children is special in this aspect, as most of them do not live in Austria, so they do not belong to this group of students in the sense of non-immigrant language and “migration background”. The aim of the study is to explore whether the principles for students with a migrant background are implemented in the case of Hungarian children, and if so, in what form.